The Effect of Sorghum Juice Concentration (Sorghum bicolor L.) on Yogurt Characteristics - Wirmadi, Erycka Putri; Ulfa, Masayu Nur; Marvie, Ilham (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2024)
Yogurt is a derivative product of milk that undergoes a fermentation process aided by bacteria during production. Various types of bacteria, such as Lactobacillus bulgaricus and Streptococcus thermophilus, are utilized in the fermentation process. Sorghum holds numerous health benefits, including contributing to the prevention of heart disease, obesity, hypertension, maintaining blood sugar levels, and preventing colorectal cancer. Additionally, sorghum contains resistant starch and oligosaccharides that are resistant to digestion by the human body, making it suitable for use in synbiotic beverages. The research aimed to analyzed the influence of different concentrations of sorghum extract on the characteristics of yogurt, including chemistry and microbiology aspects. The results of the ANOVA tests for each parameter were found to be statistically significant and markedly different. Titration of total acidity, total dissolved solids, viscosity, and total lactic acid bacteria increased with the addition of sorghum extract.